DARI KLASIKAL MENUJU VIRTUAL: Implementasi aplikasi SIAP-BK dalam Proses Konseling Bagi Guru BK di Lingkungan Kemenag Lamongan - Dinar Mahdalena Leksana; Abdul Manan (Akademika, 2021)
Guidance and counseling is an effort to provide assistance from the counselor or teacher to the counselee or students in helping students to achieve their maximum developmental tasks. In implementing counseling counseling services, counseling teachers have the main task of providing services to students, but the activities of the guidance and counseling teachers are not only that but also the activities of BK teachers in administering activities that have been carried out by BK teachers, which are no less important than service activities. Therefore it is necessary to hold training on the use of the SIAP BK application to help BK teachers make it easier to organize the administration of guidance and counseling services. So that guidance and counseling teachers can stay focused on providing guidance and counseling services without leaving the main task of the counseling teacher providing guidance and counseling services to students. This training activity is given to BK teachers in the Ministry of Religion of Lamongan Regency in stages. After conducting training on the use of the SIAP BK application, it was concluded that BK teachers could be more productive and active in providing guidance and counseling services.